REFORMULASI PENAFSIRAN RUH MENURUT ZEZEN ZAINAL ABIDIN BAZUL ASYHAB - Yasser Muda Lubis; Salman AlFarizi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
The purpose of this study is to find out and understand the meaning of the spirit in general in the Qur'an and specifically according to Zezen's Thoughts Zainal Abidin Bazul Asyhab. He is one of the Archipelago Figures, Charismatic Ulama from West Java and he is one of the Sufi figures whose thoughts in his study, especially on the study of interpretation, are considered productive and have significant and substantive contributions. The researcher describes Zezen's findings that reveal the meaning of spirit in the Qur'an by taking verses from the Qur'an, namely QS: al-Isra' verse 85 which is the basis of the polemic of the discussion about the spirit whose findings are that the discussion about the spirit is very broad. and not only half understood. The findings of the discussion of the spirit in the Qur'an are very broad and there are various meanings of the pronunciation of the spirit in the Qur'an and its relation is very important for humans to know and understand the divinity dimension that exists within themselves, especially as God's perfect creation. among other creatures through the initial creation of the spirit of Muhammad to the process of the spirit traveling to Allah as outlined in this study. In this study, it can also be seen that there are clear comparisons that are different from other thinkers, one of which is the perspective taken, namely the different patterns of thinking of each character and also the presentation is certainly different. the consequence of the perspective that the researcher takes emphasizes that this spirit is one of the very broad discussions and must be understood in depth both in theory and practice so that it can be implemented into everyday life properly and correctly